32 & 16 YEARS AGO. (Computer (00189162), 2010)
The article presents summaries of previous articles featured in the magazine dated July 1978 and July 1994. It features polyautomata, a metaphor used for reconfigurable machines and the development of design techniques to replace intuitive computer design with a set of synthesis procedures. It also features the release of 32-bit operating system named Chicago, which will be called Windows 4.0, by January 1995. Also discussed is the use of volumetric data to represent an object as a union of simple volume primitives.